Utterly amazing science - Winston, Robert M. L. (DK, Dorling Kindersley London, London, 2014)
Learn about the awe-inspiring world of science withpop-ups, pull-outs, and fantastic facts with Professor Robert Winston. Utterly Amazing Scienceis an engaging, eye-catching approach to exploring what makes the world go round. Professor Robert Winston unravels the mysteries of science alongside pop-ups, pull-outs, flaps, sliders and incredible science facts to make learning about science fun and interactive. Use push and pull sliders to feel the force! Understand the building blocks of matter with a pop-up atom or lift the flaps on the periodic table. Discover the incredible core topics in the world of science, including forces and motions, light and colour, elements and matter, andmagnets and electricity with clear explanations and fun activities to help your child understand the building blocks of science. Perfect for budding scientists with the combinationof information and interactivity, Utterly Amazing Science will leave you thoroughly blown away! Ages 7-10 years